Koulukotiin sijoitettujen nuorten psykiatrinen oirekuva ja ennuste - Manninen, Marko (Helsingin yliopisto, 2013)
Adolescents placed in reform school system are a high risk population for substance use disorders, antisocial lifestyle and severe mental illness. The aim of this thesis is to explore the psychological and psychiatric profile of the reform school adolescents, and compare the results to those of an extensive control group matched by age. In addition, the predictive value of psychological factors for later criminality and later psychiatric illness in a five-year follow-up period is studied. The data were gathered during 2004-2005. Fifty-three (M/F 33/20) adolescents participated in the study. Psychiatric symptoms were assessed by multiple questionnaires and an interview. The participants were also administered an extensive neuropsychological test battery. Background information was gathered from the reform school archives. The outcome measures for the five-year follow-up were obtained from the criminal records and hospital discharge register. The control group for the psychiatric symptoms was the Northern Finland 1986 birth cohort. A control group from a public school in Helsinki provided normative data on the cognitive test measures. According to the results, reform school adolescents suffer from a wide spectrum of psychiatric symptoms, both on internalizing and externalizing spectrum. Boys depression, adolescents social problems and prepsychotic symptoms might not be recognized by the foster parents. Many reform school adolescents have considerable difficulties in emotion processing; especially girls do not recognize depression. The reform school adolescents overall cognitive performance is weaker than in the control group. The most important deficits are found on the verbal domain. During the five-year follow-up, 75 % of reform school boys had a new entry in the criminal registry, and half of the boys had entries due to violent crime. The criminality among the reform school girls was considerably less frequent. For boys, weak verbal performance predicted both any type of criminality, and violent crime. During ...